数字技术赋能跨境贸易全链条协同:模式 重构、技术路径与运作质效. - 王 华; 王灵乐 (Journal of Xi'an Jiaotong University (Social Sciences), 2026)
Against the backdrop of economic globalization and the advancement of the Belt and Road Initiative, cross-border trade serves as a pivotal link in the dual circulation strategy. Its level of digitalization and facilitation directly impacts the quality of an open economy. Although China has achieved phased results in the digitalization of cross-border trade, the traditional "segmented collaboration" model still suffers from core pain points such as barriers to stakeholder coordination, deficiencies in process synergy, and imbalances between regulatory oversight and service coordination, making it difficult to meet the practical needs of full chain connectivity. The high compatibility between digital technologies and the holistic coordination demands of cross-border trade offers a critical pathway to overcome these bottlenecks. This study systematically analyzed the intrinsic logic and practical approaches of leveraging digital technologies to empower full-chain collaboration of cross-border trade, focusing on model reconstruction, technological pathways, and operational quality-efficiency frameworks. At the model reconstruction level, addressing traditional collaboration bottlenecks, an "Operations-Business-Management (OBM)" multi-domain data collaboration model was established to achieve effective decoupling and reorganization of "commercial flow, logistics, capital flow, and information flow". Simultaneously, a "government-enterprise" one-stop collaboration model was established to deepen the integration of government services and enterprise services. This model gave rise to two sub-modes: full-chain collaboration across business scenarios and multimodal transport collaboration. forming a comprehensive collaboration framework covering multiple entities and the entire process. Regarding technical pathways, an integrated technical system was constructed encompassing "underlying data collaboration, full-chain efficiency optimization, and full-chain supervision". Underlying data collaboration solidified a standardized, trustworthy data foundation through four core technologies: multi-domain data classification and sharing, cognitive graph construction and reasoning, intelligent trade document processing, and cross-domain modular trusted data middleware. Full-chain efficiency optimization focused on the core scenarios of "transaction-logistics-payment", utilizing three technologies commodity carbon footprint statistics and monitoring, multimodal transport logistics efficiency optimization, and supply chain financial services based on property rights information credit to achieve efficiency improvement and value enhancement. Full-chain supervision utilized dynamic credit assessment and comprehensive risk assessment technologies for cross-border trade entities to establish a "credit-driven + risk warning" regulatory framework that balances compliance and service requirements. In terms of operational quality and efficiency, digital technologies bring about systemic improvements in three dimensions: efficiency, cost, and risk. Efficiency improvements include significantly reducing document processing time, substantially shortening cross-departmental review cycles, and enabling automated multimodal transport route planning. Cost reductions stem from automation lowering labor expenses, multimodal optimization cutting logistics expenditures, and compliance alerts preventing violation losses, while resource optimization minimizes societal resource consumption. Risk prevention is achieved by improving anomaly detection accuracy through full-chain risk management models and data security technologies that meet cross-border compliance requirements, thereby ensuring collaborative security. The core value of this study lies in driving the transformation of cross-border trade from "fragmented process optimization" to "full-chain systemic collaboration" through model restructuring and technological implementation, achieving a win-win-win scenario where "enterprises benefit, governments enhance efficiency, and society saves resources". The findings provide practical guidance for corporate digital transformation and offer theoretical and empirical support for government departments to refine cross-border trade facilitation policies and build international trade channels characterized by "high efficiency, low cost, and superior service".